2015
DOI: 10.15640/jeds.v3n2a14
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Quality, Macroeconomic Policy and Economic Development in Nigeria

Abstract: This paper examines the relationship between institutional quality, macroeconomic policy, and economic development in Nigeria. We employ data from four development indicators: the prevalence of undernourishment, life expectancy at birth, the Human Development Index (HDI) and Gross Domestic Product (GDP) per-capita from 1995 to 2013 to examine the validity of the proposed framework. Our result indicates an insignificant impact of domestic institution on Nigeria development indices. Interest rate was also found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Furthermore, betterment in the quality of institutions also increases returns to education leading to higher demand for education thus enhancing the secondary school enrollment rates. This positive association has also been observed by previous studies such as Shuaibu and Timothy (2016), Okoi et al (2015), andCarmignani (2013).…”
Section: Foreign Capital Flows and Secondary School Enrolment: Role O...supporting
confidence: 88%
“…Furthermore, betterment in the quality of institutions also increases returns to education leading to higher demand for education thus enhancing the secondary school enrollment rates. This positive association has also been observed by previous studies such as Shuaibu and Timothy (2016), Okoi et al (2015), andCarmignani (2013).…”
Section: Foreign Capital Flows and Secondary School Enrolment: Role O...supporting
confidence: 88%
“…Their empirical findings demonstrated a one-way relationship between the rule of law, government effectiveness, and economic growth. Okoi et al (2015) investigated the relationship between institutional quality, macroeconomic policy, and economic development in Nigeria using the OLS technique. According to the study, domestic institutions have a negligible impact on Nigeria's development indexes.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Low labor-intensive sector productivity, such as agriculture, which employs 77% of working-age adults, has hampered inclusive and broad-based growth. Over the last decade, the agriculture sector has grown at a rate of only 4% per year (Kitole et al, 2022c;Kitole, 2023;Yusuff, 2018;Okoi, 2015;Pere, 2015;Fumbwe et al, 2021), contributing to the country's continued poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sulaiman et al (2017) used a dynamic GMM model over the period 2005 to 2013 and reported that control of corruption and governance negatively affects forest degradation in sub-Saharan Africa. Ifere et al (2015) used OLS method and found that domestic institution did not impact significantly on development indices in Nigeria in the period 1995 to 2013. Iyoboyi and Pedro (2014) used a vector error correction model to demonstrate that in the period 1961 to 2011, institutional quality has a negative relationship with macroeconomic performance in Nigeria.…”
Section: An Overview Of the Literaturementioning
confidence: 99%